Research on unequal error protection of irregular LDPC codes - MA Pi-ming; YUAN Dong-feng; YANG Xiu-mei (Tongxin xuebao)
An irregular low-density parity-check （LDPC） code with unequal error protection （UEP） property was proposed. A weight-increasing parity-check （WIPC） matrix was constructed. With systematic encoding, the important information bits in information sequence could successfully be mapped to the elite bits of an irregular LDPC code. Simulation results over AWGN and Rayleigh fading channels show that LDPC codes from WIPC matrix can achieve better UEP performance than conventional randomly constructed irregular LDPC codes.